Digging Deeper: the Politics of 'Conflict Minerals' in the Eastern Democratic Republic of the Congo. Issue 4 (November 2013) - Cuvelier, Jeroen; Diemel, Jose; Vlassenroot, Koen
Abstract : But the dominant understanding of the reasons behind Congo's war is not without critique. Different experts have raised their concerns about the too narrow scope on conflict dynamics in the DRC.